'Preferential looking' for monocular and binocular acuity testing of infants. - Atkinson, J; Braddick, O; Pimm-Smith, E (1982)
A method is described for obtaining rapid and reliable estimates of acuity in infants, for both monocular and binocular viewing. The method depends on 'preferential looking', where the infant prefers to look at a striped pattern rather than a blank screen of matched mean luminance. A staircase procedure for testing is followed, with observations being recorded by a 'blind' observer (who does not know on which of the 2 screens the striped pattern is displayed). Monocular acuity estimates have been obtained for a group of infants 3 to 4 months old with normal refractions. Many of these infants show similar acuity values in the 2 eyes, with a few showing reliable differences between the eyes. To check reliability of the method a comparison of 2 independent interleaved staircase estimates of the same eye have been made. In general this check shows highly consistent estimates for a given eye of a given infant. Nearly all infants show slightly higher acuity estimates for binocular viewing than for monocular. The possible reasons for this difference are discussed. The clinical use of such a method is reported for a number of cases. The method has been found to be useful in a variety of clinical conditions where other available tests are not possible on young infants.